Research Progress and Prospect of Extreme Water Increase by Storm Surge in Estuaries — A Case Study of Guangdong-Hong Kong-Macao Greater Bay Area - LIU Yuexuan; LI Huijing; LI Lanbin; LIU Xiaojian (Renmin Zhujiang)
Significant increases in water and extreme tide levels caused by typhoon storm surges are the primary threat to flood safety in estuarine areas,and are also the main cause of major natural disaster losses in the Guangdong-Hong Kong-Macao Greater Bay Area in recent years.This paper reveals the evolution patterns of water increase in storm surges over the years and introduces corresponding research methods.Meanwhile,it systematically reviews research achievements on the formation mechanism of extreme tide levels in storm surges from both foreign and domestic perspectives.Combined calculation models of extreme tide levels formed by astronomical tides and storm surges in China and abroad are also summarized,with a focus on achievements in dynamic mechanisms during extreme water increase in storm surges.Additionally,a two-dimensional nested mathematical model of storm surges in the South China Sea and the Pearl River Estuary is built,and the most unfavorable typhoon intensity and path are designed.The maximum water increase distribution in the Guangdong-Hong Kong-Macao Greater Bay Area is preliminarily simulated and obtained.Finally,it is urgent to put forward a set of safe,concise,and applicable formula for calculating the extreme tide levels of storm surges as soon as possible based on the understanding of the physical mechanism of the interaction between astronomical tides and storm surges.